A Holistic Model of Female Leadership in Islamic Boarding Schools: Integrating Transformational, Spiritual, and Nurturing Dimensions - Unun Zumairoh Asr Himsyah; Maulida Amirul Aulia Aulia (Al-Qalam Institue, 2026)
This study aims to examine the leadership model and educational contributions of a female leader in Islamic education. Given the limited scholarly attention to women’s leadership in Islamic boarding schools, the research focuses on understanding how leadership practices influence educational quality and student character development. This research employed a qualitative case study approach. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using an interpretive framework to identify leadership patterns and their educational impacts. The findings reveal that the leader’s approach integrates transformational, spiritual, and nurturing leadership dimensions. This model enables the effective combination of institutional management with personalized guidance for students. Policies promoting financial independence, daily discipline, and character formation demonstrate the ability to harmonize traditional Islamic values with contemporary educational demands. As a result, students develop stronger moral integrity, resilience, responsibility, and self-reliance. The study implies that a holistic and contextual leadership model can strengthen the role of Islamic educational institutions in fostering inclusive, future-oriented, and civilization-building education. It also highlights the strategic contribution of female leadership in advancing educational innovation while preserving religious and cultural values.